Assembly of an improved hybrid cascade system for complete ethylene glycol oxidation: Enhanced catalytic performance for an enzymatic biofuel cell - Franco, Jefferson Honorio [UNESP]; Bonaldo, João Victor; Minteer, Shelley D.; Andrade, Adalgisa R. de [UNESP] (Elsevier, 2022)
We report an Enzymatic Fuel Cell (EFC) combining an enzyme that can cleave carbon-carbon bonds (oxalate oxidase (OxOx)) with an organic catalyst (Pyrene-TEMPO (TEMPO = 2,2,6,6-tetramethyl piperidinyl-N-oxyl)) immobilized on the surface of modified carboxylated multi-walled carbon nanotubes (MWCNT-COOH). This combination gave a hybrid bi-catalyst electrode for complete ethylene glycol (EG) oxidation. The hybrid electrode provided ninefold enhanced catalytic activity (0.17 ± 6 × 10−3 mA cm−2) in the presence of EG as compared to the electrode in the absence of EG (0.018 ± 3 × 10−5 mA cm−2), indicating that the enzyme combined with the organic catalyst improved energy generation through deep EG electrooxidation. Electrochemical impedance spectroscopy reveals that the addition of the enzyme in the electrode containing MWCNT–COOH–Pyrene-TEMPO increased the charge transfer resistance (Rct) and the capacitance of the double layer. Long-term electrolysis for 15 h showed that the hybrid electrode presented outstanding current density and stability. The EG oxidation products were identified and quantified by high-performance liquid chromatography (HPLC-UV/RID). The results confirmed complete EG oxidation in the presence of CO2 in the solution, allowing 10 electrons to be collected from the fuel. Overall, this study illustrates the development of a simple and improved hybrid bi-catalyst electrode for promising applications in small electronic devices.
Keywords: Enzymatic biofuel cell; Ethylene glycol; Hybrid electrode; Organic catalyst; Oxalate oxidase